# 所编裴书练习参考解答封面 [购买了书的同志记得一定要邮件联系, 并加我微信, 方便更正错误. 这里更新有时会慢, 或者懒得弄.]

[There are 678 problems in total, and it really took me a lot of time in proving and typing. Some are rounting verifications, some are interesting generalizations of well-known results, while others are really chanlleging research projects. Sometimes I took one weak or more to think out only one problem. If you whish, you could just pay 333 Yuan (approximately 0.5 Yuan per one problem) to zhangzujin361@163.com via alipay (after you have paid, please send me an email to zhangzujin361@163.com with the deal serial number), then I shall send you a parcel by Ems or other express companies.]

** 1.2.2 2) 的解答中, 由极限定义知 $\dps{\vlm{n}x_n=0\lra \vlm{n}x_n=0}$.'' 改为 由极限定义知 $\dps{\vlm{n}x_n=0\lra \vlm{n}|x_n|=0}$.''

** 1.2.12 的解答最后一行, $\dps{\exp\sez{\vlm{n}\ln\sex{\sqrt[3]{1+\f{i}{n^2}}}-1}}$'' 改为 $\dps{\exp\sez{\vlm{n}\sum_{i=1}^n\sex{\sqrt[3]{1+\f{i}{n^2}}-1}\ln a}}$''.

** 1.3.3 的解答第三行, $\dps{\exp\sez{\lim_{x\to 0}\f{1}{\f{a^x+b^x+c^x}{3}}{x}\cdot \f{a^x\ln a+b^x\ln b+c^x\ln c}{3}}}$'' 改为 $\dps{\exp\sez{\lim_{x\to 0}\f{1}{\f{a^x+b^x+c^x}{3}}\cdot \f{a^x\ln a+b^x\ln b+c^x\ln c}{3}}}$''.

** 1.3.14 的解答第三行, $\dps{\lim_{x\to 0^+}\sin x^2=0}$'' 改为 $\dps{\lim_{x\to 0^+}\cos x^2=1}$''.

** 1.6.4 中, $\dps{\vlm{n}\sqrt[n]{x_n}=1}$ 改为 $\dps{\vlm{n}\sqrt[n]{x_n}=l}$.

** 3.1.19 的解答第六行, $\dps{xy^{(m+2)} +(x+1)y^{(m+2)}+(m+1)y^{(m)}=0}$'' 改为 $\dps{xy^{(m+2)} +(x+1)y^{(m+1)}+(m+1)y^{(m)}=0}$.

** 3.5.12 的解答中, 所有的 $\dps{\f{3}{2}}$ 改为 $\dps{\f{2}{3}}$.

** 4.1.3 的解答中, 第一个等号后 $\dps{\sev{\f{1}{n}\sum_{i=1}^n \int_\f{i-1}{n}^\f{i}{n} f(x)\rd x-\f{1}{n}\sum_{i=1}^n f\sex{\f{i}{n}}}}$ 改为 $\dps{\sev{\sum_{i=1}^n \int_\f{i-1}{n}^\f{i}{n} f(x)\rd x-\f{1}{n}\sum_{i=1}^n f\sex{\f{i}{n}}}}$.

** 4.1.5 的解答中, $s(x+1)=4[x+1]-2[2x+2]+1 =4[x]+2[2x]+1=s(x)$ 改为 $s(x+1)=4[x+1]-2[2x+2]+1 =4[x]-2[2x]+1=s(x)$.

** 4.1.7 的解答最后一行, $n\to\infty$ 改为 $p\to\infty$.

** 4.1.8 的解答中, $\dps{x_i=\f{i}{n}(b-a)}$ 改为 $\dps{x_i=a+\f{i}{n}(b-a)}$. $$\hj{ &=\sum_{i=1}^n\int_{x_{i-1}}^{x_i} f'\sex{\f{x_{i-1}+x_i}{2}}\sex{x-\f{x_{i-1}+x_i}{2}} +f''(\xi_i)\sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x\\ &=\sum_{i=1}^n\int_{x_{i-1}}^{x_i} f''(\xi_i)\sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x, }$$ 改为 $$\hj{ &=\sum_{i=1}^n\int_{x_{i-1}}^{x_i} f'\sex{\f{x_{i-1}+x_i}{2}}\sex{x-\f{x_{i-1}+x_i}{2}} +\f{1}{2}f''(\xi_i)\sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x\\ &=\f{1}{2}\sum_{i=1}^n\int_{x_{i-1}}^{x_i} f''(\xi_i)\sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x, }$$ $$\hj{ &\sum_{i=1}^n m_i\int_{x_{i-1}}^{x_i} \sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x \leq B_n\leq \sum_{i=1}^n M_i\int_{x_{i-1}}^{x_i} \sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x, }$$ 改为 $$\hj{ &\f{1}{2}\sum_{i=1}^n m_i\int_{x_{i-1}}^{x_i} \sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x \leq B_n\leq \f{1}{2}\sum_{i=1}^n M_i\int_{x_{i-1}}^{x_i} \sex{x-\f{x_{i-1}+x_i}{2}}^2\rd x, }$$

** 4.1.10 题目 $$\bex |\ln(1+x)-x|\leq 2x,\ \sex{|x|<\f{1}{2}} \eex$$ 改为 $$\bex |\ln(1+x)-x|\leq 2x^2,\ \sex{|x|<\f{1}{2}} \eex$$ 后面 $\dps{\int_0^1}$ 改为 $\dps{\int_a^b}$.

** 4.3.5 的解答中, $\dps{\sev{\frac{1}{2}\int_0^{2\pi} f(x)\rd \cos nx}}$ 改为 $\dps{\sev{\frac{1}{n}\int_0^{2\pi} f(x)\rd \cos nx}}$.

** 4.3.7 的解答中, $$\bex =\frac{(b-a)^2}{8}\sez{\max_{\sez{a,\frac{a+b}{2}}}|f'|,\max_{\sez{\frac{a+b}{2},b}}|f'|} \eex$$ 改为 $$\bex \leq \f{(b-a)^2}{8}\max_{\sez{a,\frac{a+b}{2}}}|f'| +\f{(b-a)^2}{8}\max_{\sez{\frac{a+b}{2},b}}|f'| \eex$$

** 4.3.26 的解答中, 第二个等式以后分母都应该有 $\pi$.

** 4.2.27 的解答中, 所有的 $\dps{\f{t}{2n}}$ 改为 $\dps{\f{t}{n}}$; $\dps{\sum_{k=0}^n}$ 改为 $\dps{\sum_{k=0}^{n-1}}$.

** 4.4.8 的解答中, 由 4.4.8'' 改为 书第 278 页例 3.4.8''.

** 4.5.10 的解答中, 最后一行少了一个积分号 $\dps{\int_0^\infty }$.

** 4.5.15 的解答中, 第而三行少了取极限 $\dps{\vlm{n}}$.

** 5.1.10 的解答中, $\dps{1-\frac{x_n}{x_{n+1}}\leq 0}$ 改为 $\dps{1-\frac{x_n}{x_{n+1}}\geq 0}$.

** 5.1.11 的解答中, 把所有的 $p_0$ 改为 $p_1$.

** 5.1.15 的解答中, $\dps{\int_)0^1}$ 改为 $\dps{\int_0^1}$.

** 5.1.24 的解答 3) 中, $n^r$ 换成 $n_k$.

** 5.2.12 的解答中, $\dps{x>0\ra \frac{\e^{-nx}}{x}=\frac{1}{ne^{nx}}}$ 改为 $\dps{x>0\ra \frac{\e^{-nx}}{x}=\frac{1}{xe^{nx}}}$.

** 5.2.16 中, $\dps{\sum{n}}$ 改为 $\dps{\vsm{n}}$.

** 5.2.21 中, $\dps{\sqrt[n]{2}}$ 改为 $\dps{\f{1}{\sqrt[n]{2}}}$.

** 5.3.2 中, $\dps{|x|<R_1\ra \dps{\vsmk{n}{0}b_nx^n\mbox{ 收敛}}}$ 改为 $\dps{|x|<R_2\ra \dps{\vsmk{n}{0}b_nx^n\mbox{ 收敛}}}$.

** 5.3.6 中, $\dps{\leq M\f{\dps{\sum_{k=1}^N a_k}}{ +}\f{\ve}{2}}$ 改为 $\dps{\leq M\f{\dps{\sum_{k=1}^N a_k}}{ \dps{\sum_{k=1}^n a_kx^k} } +\f{\ve}{2}}$. $\dps{\f{ \dps{\vsmk{n}{0}b_nx^n}}{\dps{\vsmk{n}{0}a_nx^n}-A}}$ 改为 $\dps{\f{ \dps{\vsmk{n}{0}b_nx^n}}{\dps{\vsmk{n}{0}a_nx^n}}-A}$.

** 5.3.7 中, $\dps{\vlm{n}\sez{x_1+\sum_{k=1}^{n-1}(x_{k+1}-x_k)} x_1+\vsm{k}(x_{k+1}-x_k)}$ 改为 $\dps{\vlm{n}\sez{x_1+\sum_{k=1}^{n-1}(x_{k+1}-x_k)}= x_1+\vsm{k}(x_{k+1}-x_k)}$. $\dps{x_1+cv_1^2\vsm{k} a^{2(k-1)}\f{2}{k(k+1)}}$ 以后各项都改成 乘以 $2$.

** 5.3.12 中, $\dps{\int_0^{1-\ve}\ln \f{1+x}{1-x}\cdot\f{\rd x}{x} =2\int_0^{1-\ve} \vsmk{k}{0}\f{x^{2k+1}}{2k+1}\rd x}$ 改为 $\dps{\int_0^{1-\ve}\ln \f{1+x}{1-x}\cdot\f{\rd x}{x} =2\int_0^{1-\ve} \vsmk{k}{0}\f{x^{2k}}{2k+1}\rd x}$.

** 5.3.13 中, $\dps{\f{(-1)^n t^{2n+1}}{2n+1}}$ 改成 $\dps{\f{(-1)^n t^{2n}}{2n+1}}$.

** 5.4.16 中, $\cos nx\rd x$ 改为 $\cos i x\rd x$.

** 6.2.4 中, $\dps{3+3zz_x=6y(z+xz_x)\ra z_x=\f{2yz-1}{z-2xy}.}$ 改为 $\dps{3+3z^2z_x=6y(z+xz_x)\ra z_x=\f{2yz-1}{z^2-2xy}.}$ $\dps{2f'(x^2+y^2+z^2)\sex{x+z\f{2yz-1}{z-2xy}}.}$ 改为 $\dps{2f'(x^2+y^2+z^2)\sex{x+z\f{2yz-1}{z^2-2xy}}.}$

** 6.2.8 中, $x_2^2+x_3+\sin(x_2\cdot x_3)=0$ 改为 $x_2^2+x_3+\sin(x_2\cdot x_3)=1$.

** 7.1.5 中, $\dps{\f{3\sin (\lm x)}{x^3}}$ 改成 $\dps{\f{3\sin (\lm x)}{x^4}}$; $\dps{\f{3\cos (\lm x)}{x^3}}$ 改成 $\dps{\f{3\cos (\lm x)}{x^4}}$.

** 7.4.3 中, 第二行被积函数应改为 $2xy-2x^2+x+6-2x-2y$, $2xy-2x^2+6-x-2y$.

posted @ 2017-08-23 11:12 张祖锦 阅读(...) 评论(...) 编辑 收藏